2014
DOI: 10.1039/c4ta04721d
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum–air battery based on an ionic liquid electrolyte

Abstract: This study presents a novel non-aqueous Al–air battery utilizing 1-ethyl-3-methylimidazolium oligo-fluoro-hydrogenate room temperature ionic liquid. The Al–air-RTIL system can sustain current densities up to 1.5 mA cm−2, producing capacities above 140 mA h cm−2, thus utilizing above 70% of the theoretical Al capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 35 publications
3
72
0
3
Order By: Relevance
“…[1,2] Since the revival of Li-air technology using nonaqueouse lectrolytes in 1996, this technology has generated huge interesta nd worldwide competition. [3][4][5] Although other alternatives such as Naair, [6,7] Al-air, [8,9] and even Zn-air [10] are regaining growing interest, it is now widely accepted that the successo ft hese technologies will largely rely on the development of suitable elec-trolytes that are stable against the highly reactive superoxide intermediates and capable of controlling the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Since the revival of Li-air technology using nonaqueouse lectrolytes in 1996, this technology has generated huge interesta nd worldwide competition. [3][4][5] Although other alternatives such as Naair, [6,7] Al-air, [8,9] and even Zn-air [10] are regaining growing interest, it is now widely accepted that the successo ft hese technologies will largely rely on the development of suitable elec-trolytes that are stable against the highly reactive superoxide intermediates and capable of controlling the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…[89] The Al-air battery achieves a high energy density of 6200 Wh L À 1 (2300 Wh kg À 1 ) at the current density of 1.5 mA cm À 2 with a voltage plateau at around 1.5 V (vs. Al), which is among the highest energy densities of the metal-air batteries at room temperature. The first nonaqueous Al-air battery utilizes 1-ethyl-3-methyl-imidazoliumoligo-fluoro-hydrogenated as IL and a normal porous carbon electrode as the cathode catalyst.…”
Section: Non-aqueous Aluminum-sulfur/air Batteriesmentioning
confidence: 97%
“…However, there was no clear indication regarding whether aprotic electrolytes could be used in aluminum-air batteries until it was recently reported that an EMImCl/AlCl 3 acidic solution had been developed as an innovative electrolyte for aluminum-air batteries, exhibiting current densities of up to 0.6 mAcm -2 [91]. In another study by Gelman et al [92], it was reported current densities of up to 1.5 mAcm -2 could be achieved by using EMIm(HF) 2.3 F as the electrolyte. Despite these findings, there is still a great deal of uninvestigated potential in the field of non-aqueous electrolyte research for aluminum-air batteries.…”
Section: Page 31 Of 70mentioning
confidence: 98%